Percepções sobre a matriz curricular do ENEM para a disciplina de biologia nas escolas de Santa Maria - Silva, Cristiane Brandão da (2011)
The curricula of scientific disciplines have been one of the topics discussed in various spheres related to the educational system, but also the object of scholarly study. In Brazil, the curricula have their basis in the National Curriculum Parameters (PCNs) and National Curriculum Guidelines (DCNs), which receive normative instructions from Departments of Education and undergoing adaptations in different instances to its effective implementation in the reality of each school community. Thus, although we have the same basic curriculum, we are faced with many distortions, considering socioeconomic differences in our country. Recently the National Secondary Education Examination (Enem) began to be used as a selection process for entry in public universities and now it has greater importance to the school community. Therefore, the curriculum that supports the Enem should be examined more carefully. The objective of this study is to verify if the Enem curriculum reflects what the school community of high school in Santa Maria - RS expect that should be studied in the Biology discipline. Data were collected using a structured questionnaire with a Likert scale. The questionnaire was applied to the target population consisting of parents, students and teachers from high schools in Santa Maria, with different socioeconomic profiles. Among the findings, the teachers and students revealed spontaneously concerns with the amount of content to be studied. The data shows, also, the importance of the entrance exam for private schools students, which consequently overvalue the "classics" content of the discipline at the expense of those that emphasize social issues (environmental conservation, disease, drugs, sanitation, etc...). In public schools, students and teachers complain about the excessive intricacy of some content and generally acknowledge the importance of the content of social interest. In the federal school where the students pass by a selection process to enter, there seems to be more likely to value nearly all contents. These students criticize, however, how some topics are developed. Regarding the parents who participated in the survey, there appears to be a concern with the accumulation of "knowledge" and therefore tend to give importance to quantity without many questions about how the contents are developed.